Cross-Cultural Echoes: Exploring Cultural Nuance through Student Translation Practices - Roza, Veni; Melani, Melyann; Zulfahmi, Muhammad Riko Yohansyah (Universitas Lancang Kuning, 2024)
While numerous studies have explored the methodologies of professional translators, less attention has been paid to how translation students, particularly those new to the field, navigate the complexities of translating cultural texts. This study addresses a significant gap in translation pedagogy, focusing on how advanced translation students navigate the complexities of cultural text translation, an area often overlooked compared to studies on professional translators. Employing a qualitative research design, the study analyzed the translation strategies of five advanced students tasked with translating culturally rich texts from Indonesian to English. Data were collected through semi-structured interviews and analyses of their translations. The findings reveal that 45% of the students’ strategies involved foreignization, which preserved cultural elements of the source text, while 30% used adaptation to recontextualize culturally embedded ideas for English-speaking audiences. Domestication was employed in 15% of cases to make the text more accessible, and explicit cultural explanations were used in 10% of the translations to elaborate on concepts with no direct equivalents. These results underscore the students’ conscious balancing of cultural preservation with the need for clarity. The study highlights the need to incorporate cultural competence into translation education, focusing on teaching methods that help students handle cultural nuances effectively. These findings offer valuable quantitative and qualitative insights that can inform the creation of culturally sensitive translation programs and enhance intercultural communication.